Program Pelatihan Operasional Kapal Speedboat Fiberglass Untuk Operator Kapal Tradisional Sampang-Gili Mandangin Dalam Rangka Mendukung Perkembangan Kapal Berbahan Fiberglass Di Pulau Madura - Taufan Prasetyo; Misbakhul Fatah; M. Musta’in; Aurista Miftahatul Ilmah; Desta Rifky Aldara; Fadlilatin Nailah; Mohammad Abdullah; Muhammad Arus Samudro; Astri Rino Okvitasari; Abd. Munif (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Mandangin Island is one of the islands in Sampang Regency which has an area of 1650 km 2 with a population of around 3000 people. Most of the people on this island, the majority of whom work as fishermen, generally travel around 12.2 km to Sampang City to buy daily necessities by boarding traditional wooden boats at the Tanglok Sampang port. According to information conveyed by the Head of the Sampang Regency Transportation Service, most or almost all of the passenger ships that dock at Tanglok Port are traditional wooden ships whose actual function is to transport goods, not passengers, which are quite old. The Transportation Department considers the existing ships to be less safe and comfortable and therefore require refreshing. Besides that, wood as the main material in nature is decreasing in quantity so the price is increasingly expensive. The method implemented in this community service is to carry out a fiber glass boat operational training program for traditional boat operators. With this activity, it is hoped that the continued use of fiber glass boats can begin to be used and reduce the use of wooden boats which are relatively more expensive.